1997
DOI: 10.1159/000057352
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Supplemented Very Low Protein Diet in Predialysis Patients on the Serum Albumin Level, Proteinuria, and Subsequent Survival on Dialysis

Abstract: A very low protein diet (0.3 g/kg ideal body weight) supplemented with essential amino acids (or ketoanalogues) is seldom employed at present in chronic renal failure for fear of inducing protein deficiency, especially in patients who also have the nephrotic syndrome. Nevertheless, we have used this dietary regimen in predialysis patients for a number of years. We have shown that when these patients reach the end stage, they rarely exhibit hypoalbuminemia, in contrast to the reported 25–50% hypoalbuminemia at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 28 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…It was reported that the administration of a keto acidfortified protein-restricted diet for 2-3 years in the predialysis period prevented the development of hypoalbuminemia [18].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the administration of a keto acidfortified protein-restricted diet for 2-3 years in the predialysis period prevented the development of hypoalbuminemia [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, substantial data indicate that LPDs and SVLPDs, when properly prescribed, do not engender protein-energy wasting (7,10). These findings raise the possibility that properly prescribed dietary therapy in patients approaching ESRD might reduce their mortality risk after they commence chronic dialysis treatment, a thesis that would seem to be well worth testing (45,46).…”
Section: Benefits and Safety Of Diets For Deferring Dialysis By Amelimentioning
confidence: 99%
“…Protein restriction at higher levels of GFR may also ameliorate more subtle uremic symptoms. Current data suggest that patients need a minimum GFR level-possibly a urea clearance $2-3 ml/min per 1.73 m 2 -to do well with dietary therapy (46). Patients being considered for dietary therapy probably should not suffer from severe acute or chronic catabolic illness, should be able to understand the dietary therapy, should Table 3.…”
Section: Future Directionsmentioning
confidence: 99%
“…Quite the contrary, as we have indicated, without dietary therapy, the risk of advanced CKD patients developing PEW is quite high [7,8,13,35]. On the other hand, advanced CKD patients who do not have superimposed catabolic illnesses and who adhere to well-designed LPDs or SVLPDs are at low risk for developing severe PEW, and most appear to develop little or no PEW [2,9,36]. Although there are no randomized prospective controlled studies of the effect of dietary therapy in advanced CKD patients on survival.…”
mentioning
confidence: 91%
“…Although there are no randomized prospective controlled studies of the effect of dietary therapy in advanced CKD patients on survival. Several post-facto observational studies suggest that the association between mortality rate after commencing chronic dialysis treatments and prescription of SVLPDs to CKD patients is not increased mortality and may be reduced [36,37].…”
mentioning
confidence: 99%